How interaction molds semantics: The mood functions of Chinese “sum-up” adverbs - Song, Jingyao (Frontiers in Psychology, 2022)
“Hezhe” (合着), “ganqing” (敢情), and “nao le bantian” (闹了半天) are common mood expressions in modern Chinese which have a common function of summarizing the information before (so called ‘sum-up’) as well as similar pragmatic functions. Study on these mood adverbs could reveal how the interactional mechanism molds the original semantic meanings of mood words and leads to new pragmatic functions. Five verbal corpora are applied to collect the real materials of usage containing the above three mood adverbs. Functional analysis and data statistics have been carried out to categorize the pragmatic functions of these words, calculate their distributions, and reconstruct their evolutional approach through an interactional perspective. We have found a core theoretical viewpoint that the similar functions of the three words emerged through the same pragmatic mechanism called “violation”. These functions are: (1) “unexpectation” from the violation of psychological expectation; (2) “criticism” from the violation of universal principles; (3) “humor” from the violation of communicative principles. A statistic work of several corpora showed that these functions of the above three words appear broadly in verbal materials, with differences in their proportions according to the communication types and genres. In Chinese teaching to speakers of other languages, more attention should be paid to these words stemming from dialects, especially during intermediate and advanced levels.